My family and other animals - Durrell, Gerald (London : Collins, 2006)
The author presents a comical memoir of his family's five years living on the Greek island of Corfu and describes the island's flora and fauna.
Keywords: Natural history -- Greece -- Corfu island; Corfu island (Greece) -- Description and travel